2020
DOI: 10.3390/ijerph17041398
|View full text |Cite
|
Sign up to set email alerts
|

Association between Neighborhood Environment and Quality of Sleep in Older Adult Residents Living in Japan: The JAGES 2010 Cross-Sectional Study

Abstract: Poor sleep is associated with lifestyle, however, few studies have addressed the association between sleep quality and the neighborhood environment. This study aimed to investigate the associations between living environment factors and sleep quality in older people. Participants were community-dwelling people aged ≥65 years who participated in the 2010 Japanese Gerontological Evaluation Study. The data of 16,650 people (8102 men, 8548 women) were analyzed. Sleep quality (good or poor) was evaluated using a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Sleep quality is one of the most important aspects for keeping fine physical health status in older adults. Together with exercise and diet, sleep has been identified as a key lifestyle factor to maintain the subjective psychological well-being among elder population ( Watanabe et al, 2020 ). Surveys have indicated that poor quality of sleep was a strong risk factor for psychiatric disorders ( Baglioni et al, 2011 ; Cable et al, 2017 ), such as anxiety and depression, and even dementia and cognitive impairment ( Sexton et al, 2017 ; Suh et al, 2018 ; Cordone et al, 2019 ; Cordone and De Gennaro, 2020 ) in the older population.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep quality is one of the most important aspects for keeping fine physical health status in older adults. Together with exercise and diet, sleep has been identified as a key lifestyle factor to maintain the subjective psychological well-being among elder population ( Watanabe et al, 2020 ). Surveys have indicated that poor quality of sleep was a strong risk factor for psychiatric disorders ( Baglioni et al, 2011 ; Cable et al, 2017 ), such as anxiety and depression, and even dementia and cognitive impairment ( Sexton et al, 2017 ; Suh et al, 2018 ; Cordone et al, 2019 ; Cordone and De Gennaro, 2020 ) in the older population.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies have also reported nonsignificant associations between social cohesion and sleep outcomes after adjustment for confounders (D. A. Johnson et al, 2016; Nomura et al, 2010; Troxel et al, 2018; Watanabe et al, 2020). Likely reasons for such discrepant findings in the literature could be that much previous research has examined neighborhood factors within predominantly high-density urban settings, compared with the more geographically diverse and representative sample examined in this study.…”
Section: Discussionmentioning
confidence: 89%
“…24 Therefore, we used PR calculated using multivariate Poisson regression analysis modified using sandwich estimation, 25 which previous reports have shown does not cause overestimation and underestimation whenever incidence of outcomes is high. 26 , 27 Analyses were performed with the unadjusted model (crude) and the model adjusted for sex, age, BMI, disease history, medication use, depressive symptoms, perceived chewing ability, smoking, physical activity levels, living alone, food service use, years of education, employment status, and driving license (adjusted model). These covariates were included because they are related to dietary habits 6 and are treated as adjustment factors in epidemiological nutrition studies.…”
Section: Methodsmentioning
confidence: 99%